Prevalence of sport specialization in high school athletics - Bell, D. R.; Post, E. G.; Trigsted, S. M.; Hetzel, S.; McGuine, T. A.; Brooks, A. (The American Journal of Sports Medicine, 2016)
Background: The prevalence of sport specialization in high school athletes is unknown. This information is needed to determine the scope of this issue in an active population. Purpose: To determine the prevalence of sport specialization in high school athletes and to determine if specialization is influenced by classification method, year in school, sex, and school size. A secondary purpose was to determine if highly specialized athletes would be more likely to report a history of lower extremity injuries. Study Design: Cross-sectional study; Level of evidence, 3. Methods: High school athletes between the ages of 13 and 18 years from 2 local high schools completed both a sport specialization survey and an injury history survey. Athletes were classified into low, moderate, or high specialization groups using a recently developed 3-point system and were also classified using a self-classification method. Results: A total of 302 athletes completed the surveys and were classified as low specialization (n = 105, 34.8%), moderate specialization (n = 87, 28.8%), or high specialization (n = 110, 36.4%). Athletes from the small school were more likely to be classified in the low specialization group (low, 43%; moderate, 32%; high, 25%) compared with those from the large school (low, 26%; moderate, 26%; high, 48%) (P < .001). Athletes in the high specialization group were more likely to report a history of overuse knee injuries (n = 18) compared with moderate (n = 8) or low specialization (n = 7) athletes (P = .048). Athletes who trained in one sport for more than 8 months out of the year were more likely to report a history of knee injuries (odds ratio [OR], 2.32; 95% CI, 1.22-4.44; P = .009), overuse knee injuries (OR, 2.93; 95% CI, 1.16-7.36; P = .018), and hip injuries (OR, 2.74; 95% CI, 1.09-6.86; P = .026). Using the self-classification method, more participants self-classified as multisport (n = 213, 70.5%) than single sport (n = 89, 29.5%). Athletes from the small school were more likely to classify themselves as multisport (n = 128, 86%) (P < .001) than those from the large school (n = 85, 56%). There were no differences in the history of hip, knee, or ankle injuries between athletes who self-classified as single sport (hip: n = 10, 3%; knee: n = 19, 6%; ankle: n = 35, 12%) versus those who self-classified as multisport (hip: n = 45, 8%; knee: n = 23, 15%; ankle: n = 98, 33%) (P > .370). Conclusion: Classification method and school size influenced the prevalence of specialization in high school athletes. Highly specialized athletes were more likely to report a history of overuse knee or hip injuries. Participating in a single sport for more than 8 months per year appeared to be an important factor in the increased injury risk observed in highly specialized athletes.